Exploring Tectona grandis Linn. f. Leaf Extract as a Functional Feed Additive with Antioxidant and Nutraceutical Potential for Livestock - Montri, Nattaya; Wanapat, Metha; Kang, Sungchhang; Cheas, Seangla; Cherdthong, Anusorn; Gunun, Pongsatorn; Gunun, Nirawan; Foiklang, Suban; Kongmun, Phongthorn; Srithat, Dutsadee; Tongkasee, Pongsathorn; Polyorach, Sineenart (My University, 2025)
This study investigated the phytochemical composition, antioxidant activity, and safety of Tectona grandis leaf extracts at four maturity stages. Ethanolic extracts were screened for secondary metabolites and analyzed using GC–MS, together with heavy metal determination, phenolic profiling, and antioxidant assays. Preliminary phytochemical screening revealed the presence of alkaloids, flavonoids, glycosides, tannins, saponins, and coumarins, with clear variation among leaf stages. GC–MS analysis detected multiple bioactive constituents, including phytol, n-decanoic acid, and heptadecenal. These compounds have been previously reported to exhibit antioxidant, antimicrobial, and anti-inflammatory properties. Heavy metal analysis showed very low cadmium concentrations (0.001–0.004 mg/kg), undetectable lead levels (<LOD), and trace levels of arsenic concentrations (0.012–0.018 mg/kg), all of which were within safe limits for plant materials. Quantitative assays demonstrated that mature leaves contained the highest total phenolic (8.751 ± 0.018 mg GAE/g DW), total flavonoid (0.359 ± 0.017 mg QE/g DW), and condensed tannin (0.303 ± 0.000 mg CE/g DW) contents. Correspondingly, mature-leaf extracts exhibited the greatest antioxidant capacity, showing 95.88 ± 0.12% inhibition of oxidant activity. The ethanolic extracts exhibited IC50 values ranging from 22.93–50.35 mg/mL, whereas the ascorbic acid standard showed an IC50 of 0.0767 mg/mL, confirming the expected lower potency of crude plant extracts. The strong correlation between phenolic accumulation and antioxidant activity suggests enhanced defense against oxidative stress. The absence of detectable heavy metal contamination, together with the high polyphenolic content, suggests that T. grandis leaves may serve as a safe natural source of antioxidants. These findings demonstrate the strong antioxidant potential of T. grandis leaf extracts, providing a basis for future studies evaluating their functional applications in biological systems.
Keywords: antioxidant activity; functional feed; livestock nutrition; phytochemical profile; Tectona grandis